Theoretical calculation and measurement accuracy of Cerenkov optic-fiber dosimeter under electron and photon radiation therapies. (March 2018) - Zhang, Xudong; Tang, Xiaobin; Shu, Diyun; Gong, Chunhui; Geng, Changran; Ai, Yao; Yu, Haiyan; Shao, Wencheng
Abstract: This work aimed to study the mechanism and understand the influencing factors of measurement accuracy for the Cerenkov optic-fiber dosimeter under electron and photon radiation therapies. Through the Geant4 calculation, we determined responses between Cerenkov photon numbers recorded by the measurement device and the dose deposited in the fiber and found responses differed for electron and photon beam irradiations. For electron beams, the relative Cerenkov photon number recorded by the device agreed well with the relative dose for the depths after the maximum dose depth, but differed before that depth. For the photon beams, the relative Cerenkov photon number showed good agreement with the relative dose for all depths. Considering the transmission efficiency of the Cerenkov radiation in the fiber, energy spectra and angular distributions of electrons were analyzed to explain the response difference. For the photon beams, energy spectra and angular distributions of electrons changed less in various phantom depth than electron beams, therefore, better response was observed for photon beams. Besides, the influences of fiber parameters (i.e. diameter, refractive index, and material) were investigated. With the increase of the core diameter, the transmission efficiency of Cerenkov radiation changed slightly but the Cerenkov photon numbers produced in the fiber increased by square. With smaller ratio of cladding/core refractive index or using PMMA as the core materials, Cerenkov photon numbers recorded by the device could also be increased. This study could provide better understanding of the Cerenkov optic-fiber dosimeter and promote its development. Highlights: The intrinsic mechanism of Cerenkov optic-fiber dosimeter was studied with Geant4. Responses between Cerenkov radiation and dose differ under electron and photon beams. Energies and angles of electrons were analyzed to explain the response difference. Influences of fiber parameters were investigated to improve the measurement accuracy.